Mathematical model to predict the dry matter intake of dairy cows on pasture - SÁNCHEZ-PÉREZ, ROSARIO; MARIEZCURRENA, MARÍA D; ELGHANDOUR, MONA M M Y; MELLADO, MIGUEL; CAMACHO-DIAZ, LUIS M; CIPRIANO-SALAZAR, MOISÉS; SALEM, ABDELFATTAH Z M (The Indian Journal of Animal Sciences, 2023)
In pasture-based dairy systems, there is a close relationship between milk production and dry matter intake (DMI), hence the importance of measuring these variables, although obtaining this information implies high labour and costs. The objective of this study was to design a mathematical model to predict DMI for grazing dairy cows. This model was based on the basic principle of the fill-unit system. In this scheme, cows and feedstuffs were described in terms of feed intake capacity (FIC) and fill (unit/amount of feed), respectively. The FIC was determined by the animal's ability to regulate feed intake which depends on factors such as body size, age and lactation status. The "fill" was determined by the nutritional properties of the feedstuff such as its dry matter (DM) digestibility and crude protein (CP) content, among others. In the design of the model, ad lib. feed consumption was assumed. Parity, state of lactation and gestation were considered to estimate the cow ingestion capacity. Satiety values (SV) were determined for Festuca arundinacea and Lolium multiflorum and these values were incorporated into the model, including DM, CP, neutral detergent fibre (NDF) and in vitro digestible organic matter (dOM). The fixed parameters of the model were determined by adjusting a polynomial regression to the data from three experiments with lactating Holstein cows from Baja California, Mexico (n=30).The model allows predicting DMI, using as inputs, easily measured data and does not require knowing daily milk yield (MY) or body weight (BW), so the model is practical and consistent. The results obtained from the model were satisfactory because they were similar to those attained experimentally. Average DMI was 21.68 kg/d in one group and 23.44 kg/d in the other; when applying the model, we obtained an estimate of 22.82 kg/d for a cow with characteristics similar to those of the cows under study.